Reliability of smartphone‐based gait measurements for quantification of physical activity/inactivity levels. Issue 6 (20th November 2017) - Ebara, Takeshi; Azuma, Ryohei; Shoji, Naoto; Matsukawa, Tsuyoshi; Yamada, Yasuyuki; Akiyama, Tomohiro; Kurihara, Takahiro; Yamada, Shota
Abstract : Objectives: Objective measurements using built‐in smartphone sensors that can measure physical activity/inactivity in daily working life have the potential to provide a new approach to assessing workers' health effects. The aim of this study was to elucidate the characteristics and reliability of built‐in step counting sensors on smartphones for development of an easy‐to‐use objective measurement tool that can be applied in ergonomics or epidemiological research. Methods: To evaluate the reliability of step counting sensors embedded in seven major smartphone models, the 6‐minute walk test was conducted and the following analyses of sensor precision and accuracy were performed: 1) relationship between actual step count and step count detected by sensors, 2) reliability between smartphones of the same model, and 3) false detection rates when sitting during office work, while riding the subway, and driving. Results: On five of the seven models, the inter‐class correlations coefficient (ICC (3, 1)) showed high reliability with a range of 0.956‐0.993. The other two models, however, had ranges of 0.443‐0.504 and the relative error ratios of the sensor‐detected step count to the actual step count were ±48.7%‐49.4%. The level of agreement between the same models was ICC (3, 1): 0.992‐0.998. The false detection rates differed between the sitting conditions. Conclusions: These results suggest the need for appropriate regulation of step counts measured by sensors through means such as correction or calibration with a predictive model formula in order to obtain the highly reliable measurement results that are sought in scientific investigation.